Direct measurement of free radicals in the brain cortex and the blood serum after nociceptive stimulation in rats - Rokyta, Richard; Stopka, Pavel; Holecek, Václav; Krikava, Karel; Pekárková, Ivana (Neuro endocrinology letters, 2004)
The concentrations of ROS were measured in samples of the sensorimotor brain cortex and in the rat blood. We measured the following parameters: The six lines spectra, nitroxide radical, free hydroxyl radical and singleton oxygen. Their concentration was measured under physiological conditions, after the nociceptive stimulation and after the application of melatonin, both in normal and stimulated animals. In the brain cortex only the singleton oxygen decreased after the nociceptive stimulation, whereas the nitroxide radicals and six lines spectra increased. The free hydroxyl radicals did not change significantly. In the blood serum the six lines spectra and nitroxide radical increased, the concentration of the free hydroxyl radicals did not change. Melatonin increased both the hydroxyl and nitroxide radicals. There was a non-significant decrease in the six lines spectra. The estimation of ROS can be used as a tool for detecting metabolic changes and the consequences of different environmental influences, in our case the influence of nociception and melatonin.
Keywords: Analysis of Variance; Animals; Thiobarbituric Acid Reactive Substances; Rats, Wistar; Melatonin; oxidy dusíku; somatosenzorické korové centrum; Free Radicals; hydroxylový radikál; sérum; Reactive Oxygen Species; Singlet Oxygen; Somatosensory Cortex; bolest; analýza rozptylu; Male; melatonin; reaktivní formy kyslíku; krysa rodu Rattus; Pain; Serum; mužské pohlaví; zvířata; singletový kyslík; látky reagující s kyselinou thiobarbiturovou; Nitrogen Oxides; Rats; Hydroxyl Radical; volné radikály; potkani Wistar